2014
DOI: 10.1136/jech-2014-204615
|View full text |Cite
|
Sign up to set email alerts
|

Socioprofessional trajectories and mortality in France, 1976–2002: a longitudinal follow-up of administrative data

Abstract: Strong associations between professional trajectories and mortality from different causes of death were found. Long exposure to lower socioeconomic conditions was associated with increased mortality risk from various causes of death. The results also suggest gradual associations between transition rates and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
10
1
1
Order By: Relevance
“…The choice of having more robust categories, keeping aggregated ESeC classes 7, 8 and 9 (low grade non-manual, skilled manual and unskilled manual workers), may have led to an underestimation of the actual occupational social gradient, likely of magnitude similar to that for education, considering the relative proportions of these workers’ groups and the differences in mortality observed between them in other studies [3,5,12,28,65,70]. Again, the small and non-significant occupational gradient in mortality found among women seems in contrast with the higher risks observed in several other studies investigating mortality [5,65,7175] or morbidity [7,76,77], although in most studies the gradient was lower than among men and in some others no or only slight increases in risk were found [70,7881]. The shallower social gradient observed among women, compared to other reports in the literature, appears difficult to explain and may be related to specific features of some of the cohorts examined (e.g.…”
Section: Discussioncontrasting
confidence: 67%
“…The choice of having more robust categories, keeping aggregated ESeC classes 7, 8 and 9 (low grade non-manual, skilled manual and unskilled manual workers), may have led to an underestimation of the actual occupational social gradient, likely of magnitude similar to that for education, considering the relative proportions of these workers’ groups and the differences in mortality observed between them in other studies [3,5,12,28,65,70]. Again, the small and non-significant occupational gradient in mortality found among women seems in contrast with the higher risks observed in several other studies investigating mortality [5,65,7175] or morbidity [7,76,77], although in most studies the gradient was lower than among men and in some others no or only slight increases in risk were found [70,7881]. The shallower social gradient observed among women, compared to other reports in the literature, appears difficult to explain and may be related to specific features of some of the cohorts examined (e.g.…”
Section: Discussioncontrasting
confidence: 67%
“…stable high/low and upward/downward movements). Studies using these methodologies have for example found that mobile people have a higher risk of all-cause mortality compared to non-mobile individuals [17] or to the stable in the highest class [18, 19]. Similarly, a downwardly mobile trajectory has been found to be more detrimental for mental health than being stable [20], and improvements in occupational prestige across mid-life has been linked to a more favorable health development [21].…”
Section: Introductionmentioning
confidence: 99%
“…A French study conducted on a semipublic and private sector population showed that men with high transition rates between different occupational groups had higher mortality rates. 28 Anticipation of job loss has also been shown to negatively affect health status, even before the event has taken place. 29 Norwegian agriculture has experienced extensive changes during the last decades, as in most developed countries, 18 which have led to large numbers of farmers leaving the occupation, while the size of the average farm grows bigger.…”
Section: Discussionmentioning
confidence: 99%